School Social Work: Now More Than Ever - Michael S. Kelly (International Journal of School Social Work, 2020)
We are excited to publish our 5th volume of the International Journal of School Social Work, marking five continuous years of the journal's publication. This issue is arriving at a crucial time for our schools and communities around the world, and in this brief essay, I argue that it's never been a more exciting and consequential time to be a school social worker.
Keywords: school social work; social justice; anti-racist education; evidence-informed practice; open-access